2021
DOI: 10.1186/s12872-021-01869-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between hyperhomocysteinemia and the presence and severity of acute coronary syndrome in young adults ≤ 35 years of age

Abstract: Background The prevalence of acute coronary syndrome (ACS) continues to increase among young Chinese adults. Homocysteine (HCY) has been suggested as a promoter of atherosclerosis leading to coronary artery disease (CAD). Yet, it remains uncertain whether HCY is associated with the ACS and the severity of coronary artery stenosis in young adults. Methods Young patients (18–35 years of age) diagnosed with ACS who underwent coronary angiography (CAG)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
6
1
1
Order By: Relevance
“…HHcy demonstrated a higher sensitivity (93.1%), accuracy (90.0%), and specificity (86.1%) for obstructive CAD compared to nonobstructive CAD [87]. Sun et al (2021) analyzed whether HHcy is associated with acute coronary syndrome (ACS) and the severity of coronary artery stenosis in young Chinese adults. Young ACS subjects showed a greater prevalence of HHcy when compared with non-CAD individuals.…”
Section: Hhcy and Coronary Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…HHcy demonstrated a higher sensitivity (93.1%), accuracy (90.0%), and specificity (86.1%) for obstructive CAD compared to nonobstructive CAD [87]. Sun et al (2021) analyzed whether HHcy is associated with acute coronary syndrome (ACS) and the severity of coronary artery stenosis in young Chinese adults. Young ACS subjects showed a greater prevalence of HHcy when compared with non-CAD individuals.…”
Section: Hhcy and Coronary Artery Diseasementioning
confidence: 99%
“…Young ACS subjects showed a greater prevalence of HHcy when compared with non-CAD individuals. In addition, HHcy in young ACS patients was linked with the severity of coronary artery stenosis, characterized by increased prevalence of multi-vessel disease, reduced value of left ventricular ejection fraction, and ST-segment elevation myocardial infarction (STEMI) [88]. Another study investigated the linkage between vitamin D deficiency and serum Hcy levels with the extent of CAD.…”
Section: Hhcy and Coronary Artery Diseasementioning
confidence: 99%
“…High levels of homocysteine are not only associated with the severity of vascular disease but are also associated with an increased risk of sudden events, such as MI and stroke [13,14]. A recent study that included 1103 young participants (18-35 years of age) demonstrated that hyperhomocysteinemia was an independent predictor of ACS after adjusting for traditional confounders [15]. Moreover, young ACS patients with hyperhomocysteinemia had an increased prevalence of STEMI, MVD, decreased LVEF and higher Gensini Scores in ACS patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, some controversy exists regarding the causal role of Hcy in CAD pathogenesis, since lowering Hcy levels in patients with CAD has not shown any benefit and common genetic variants that influence Hcy levels are not associated with risk of CAD [ 21 , 22 ]. Nevertheless, several observational studies found HHcy, as an important marker, was significantly associated with severe CAD in younger patients [ 6 , 23 ]. In this study, the relationship between concentrations of Hcy and the severity of coronary artery stenosis was also investigated, which showed that serum Hcy levels were positively associated with angiographic severity expressed by Gensini Score ( β 0.302; 95% CI 0.141–0.462; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%